Who pushes the buttons? Investigating the regulatory governance of retail electricity tariff setting in South Africa through institutional analysis and development - Kelly, Patrick (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2015.